The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00264-012-1669-4
|View full text |Cite
|
Sign up to set email alerts
|

Modern management of patellar instability

Abstract: Recurrent patellofemoral instability is a disabling condition, attributed to a variety of anatomical aetiologies. Trochlear dysplasia, patella alta, an increased tibial tubercle trochlear groove distance of greater than 20 mm and soft tissue abnormalities such as a torn medial patellofemoral ligament and inadequate vastus medialis obliquus are all factors to be considered. Management of this condition remains difficult and controversial and knowledge of the functional anatomy and biomechanics of the patellofem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 104 publications
0
41
0
1
Order By: Relevance
“…(3,5,7) Using the Insall-Salvati method, patella alta is present when the length of the patellar tendon divided by the maximal diagonal length of the patella on a lateral knee radiograph produces a ratio of more than 1.2 (normal ratio: 1.0) (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(3,5,7) Using the Insall-Salvati method, patella alta is present when the length of the patellar tendon divided by the maximal diagonal length of the patella on a lateral knee radiograph produces a ratio of more than 1.2 (normal ratio: 1.0) (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…(5) A borderline measurement is between 15 mm and 20 mm; when the TT-TG distance exceeds 20 mm, it is nearly always associated with patellar instability. (5,7) Lateral patellar dislocation, which most commonly affects adolescent females, usually occurs when the aforementioned predisposing factors are present. (1,5,12) It most often results from a twisting injury with knee flexion, as the femur rotates internally on a fixed tibia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported a frequency of cartilage defects between 11 % and 36 % located on the patella, with a mean size of 2.1 cm 2 [1][2][3]. These defects can result from macrotrauma and repetitive microtrauma, are often associated with abnormal patellofemoral stress due to dysplastic morphology of the trochlea groove, and impairment of the soft tissue static stabilisers [4]. Cartilage defects can also occur in combination with varus and valgus malalignment of the tibiofemoral axis and rotational differences in femoral version [5].…”
Section: Introductionmentioning
confidence: 99%
“…Over one hundred different surgical techniques exist in the treatment of patellar instability yet no gold standard has emerged in the literature [1]. Fulkerson osteotomy technique was designed to restore abnormal force vectors on the patella and decrease pressure on involved cartilage [2].…”
Section: Introductionmentioning
confidence: 99%